Analysis of mathematical communication abilities of senior high school students in linear programming material - Ali, M K; Martadiputra, B A P (Journal of physics. Conference series, 2021)
This article is the result of research that aims to analyze the students’ mathematical communication abilities in mathematics to the subject of linear programming. The research was conducted using qualitative approach with case study method. The subjects were five high school students in Science program. Data communication students’ mathematical ability is obtained by using tests and interviews. The results showed the ability of students’ mathematical verbal communication is good because students can explain clearly and systematically to answer written in the worksheet. But the student’s written mathematical communication ability are lacking in explaining the mathematical model, the use of symbols is less precise, and the writing is less systematic.